Resensi Buku: The Living Company - Ayu Chairina Laksmi; Suwarsono Muhammad (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2003)
Book ReviewJudul buku : The Living CompanyPenulis : Arie de GeusPengantar : Peter M. SengePenerbit : Harvard Business School PressTahun terbit : 1997Tebal : xiv + 214 hal